2000
DOI: 10.1067/mcp.2000.110216
|View full text |Cite
|
Sign up to set email alerts
|

Duration of effect of grapefruit juice on the pharmacokinetics of the CYP3A4 substrate simvastatin

Abstract: When simvastatin is taken 24 hours after ingestion of "high-dose" grapefruit juice, the effect of grapefruit juice on the AUC of simvastatin is only about 10% of the effect observed during concomitant intake of grapefruit juice and simvastatin. The interaction potential of even high amounts of grapefruit juice with CYP3A4 substrates dissipates within 3 to 7 days after ingestion of the last dose of grapefruit juice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(83 citation statements)
references
References 16 publications
5
73
1
4
Order By: Relevance
“…The prolongation of the interaction is consistent with the pharmacological mechanism of the interaction, since biosynthesis of a new enzyme is necessary. Up to 3 days persistence of the juice impact is reported (Takanaga et al, 2000); however, it appears that an interval of 24 h between ingestion of grapefruit juice and a drug can usually prevent a potential clinically relevant interaction (Lilja et al, 2000b).…”
Section: Amounts and Timingmentioning
confidence: 99%
“…The prolongation of the interaction is consistent with the pharmacological mechanism of the interaction, since biosynthesis of a new enzyme is necessary. Up to 3 days persistence of the juice impact is reported (Takanaga et al, 2000); however, it appears that an interval of 24 h between ingestion of grapefruit juice and a drug can usually prevent a potential clinically relevant interaction (Lilja et al, 2000b).…”
Section: Amounts and Timingmentioning
confidence: 99%
“…38 It may be concluded that the interaction between grapefruit juice and statins does not represent a great concern, unless Ͼ1 quart per day of juice is consumed. 37 …”
Section: Statin Interactions With Cyp450 Inhibitorsmentioning
confidence: 99%
“…36 The interaction potential of even high amounts of grapefruit juice with CYP3A4 substrates dissipates within 3 to 7 days after ingestion of the last dose of juice. 37 However, daily consumption of a glass of regular-strength grapefruit juice has a minimal effect on plasma statin concentrations (approximately 30% to 40% increase) after a 40-mg evening dose of lovastatin. 38 It may be concluded that the interaction between grapefruit juice and statins does not represent a great concern, unless Ͼ1 quart per day of juice is consumed.…”
Section: Statin Interactions With Cyp450 Inhibitorsmentioning
confidence: 99%
“…Moreover, the effect on simvastatin concentration is lower when simvastatin is taken 24 h after ingestion of high amounts of grapefruit juice, compared with concomitant intake of grapefruit juice and simvastatin. This effect dissipates within 3 to 7 days after ingestion of the last dose of grapefruit juice (Lilja et al, 2000). Although grapefruit juice also increases the AUC of atorvastatin, the actual increase in activity is low, probably because of a simultaneous effect of decreasing the AUC of active metabolites of atorvastatin (Saito et al, 2005).…”
mentioning
confidence: 99%